Do Components of Management Information Systems Play a Role in achieving the Quality of Health Services in Bahrain? - Mohamed Bader Abdulla Al-Haddad; Marwan Mohamed Abdeldayem; Horiya Mohamed Ahmed Al Deeb; Maryam Abdul Aziz Al-Thawadi (Global Journal of Management and Business Research, 2022)
The aim of this research is to identify the role of the components of management information systems MIS Hardware software personnel and data components in achieving the quality of the health services at Salmaniya Medical Complex in the kingdom of Bahrain A straightforward random sample method was used to conduct a survey of 401 employees The results of the questionnaire survey which were distributed to a representative sample of employees serve as the foundation for the analysis at Salmaniya Medical Complex in the Kingdom of Bahrain The research hypothesized that there is a positive significant role for the components of management information systems Hardware software personnel and data components in achieving the quality of health services at Salmaniya Medical Complex in the Kingdom of Bahrain